Robert Ludlums The Arctic Event - Ludlum, Robert 1927-2001. (New York : Vision, 2012)
"On a remote island in the Canadian Arctic, researchers discover the wreckage of a mysterious aircraft, which the Russian Federation admits is a Soviet strategic bomber that disappeared more than fifty years ago while carrying two metric tons of weaponized anthrax. Desperate to prevent a political firestorm, the U.S. president dispatches a Covert-One team led by Lieutenant Colonel Jon Smith to the crash site. But others have reached the frigid, windswept island first, including an international arms dealer, his crew of vicious mercenaries, and Russian agents who are willing to kill to protect other deadly secrets within the hulk of the lost bomber. Trapped in a polar wilderness, Smith and his team find themselves fighting a savage war on two fronts--against an enemy they can see and another hiding within their own ranks"--P. [4] of cover.
"Series created by Robert Ludlum."
Keywords: Smith, Jon -- (Fictitious character) -- Fiction; Airplanes, Military -- Accidents -- Canada, Northern; Fiction; World War, 1939-1945 -- Aerial operations, Soviet; United States -- Foreign relations -- Russia (Federation); Fiction; Russia (Federation) -- Foreign relations -- United States; Fiction; Arctic regions -- Fiction; Thrillers (Fiction)